2008
DOI: 10.1007/s10461-008-9460-7
|View full text |Cite
|
Sign up to set email alerts
|

Gay Men Who Engage in Group Sex are at Increased Risk of HIV Infection and Onward Transmission

Abstract: Among 746 participants in the Three or More Study (TOMS) of gay men who engaged in group sex in the previous 6 months, 22.4% reported unprotected anal intercourse (UAI) with any partners they did not know to be the same HIV serostatus as themselves. Not knowing oneself to be HIV-negative, not having a clear intention to use condoms, and more frequent group sex were independently associated with UAI. This study shows that gay men who engage in group sex represent an important priority for targeted HIV preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 16 publications
7
35
1
Order By: Relevance
“…This is because HIV infection is unlikely to have reached a high level of saturation among these subgroups and HIV transmission will therefore be more efficient if these networks are breached. MSM particularly at risk in this respect are likely to include those engaging in unprotected anal intercourse with multiple partners, [30][31][32][33] especially those who do so in group sex contexts, 34 and MSM with an STI. 35 At the same time, since data are lacking on patterns of assortativity and dissortativity among MSM in New Zealand -which would help quantify the degree of sexual mixing between individuals with and without these characteristicsthe promotion of 'universal precautions' through condom use should remain a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…This is because HIV infection is unlikely to have reached a high level of saturation among these subgroups and HIV transmission will therefore be more efficient if these networks are breached. MSM particularly at risk in this respect are likely to include those engaging in unprotected anal intercourse with multiple partners, [30][31][32][33] especially those who do so in group sex contexts, 34 and MSM with an STI. 35 At the same time, since data are lacking on patterns of assortativity and dissortativity among MSM in New Zealand -which would help quantify the degree of sexual mixing between individuals with and without these characteristicsthe promotion of 'universal precautions' through condom use should remain a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…142 HIV risk factors identified in Australia and overseas may indicate the need for more frequent testing in MSM and include: receptive unprotected anal intercourse, higher numbers of male sexual partners, IDU and noninjecting drug use during sex (including the use of amphetamines with oral erectile dysfunction medications), engaging in group sex, other (especially anal) STIs, sex with HIV-positive partners and high viral load in those partners. 133,[143][144][145] However, although identifying risk factors for HIV is important for targeted testing, one in eight HIV diagnoses in Australia may be missed by offering risk-based HIV testing only. 146 Annual HIV testing is recommended for MSM by the US Centers for Disease Control, 90 although only 60% of US MSM report being tested for HIV in the previous 12 months.…”
Section: Hivmentioning
confidence: 99%
“…Group sex events (GSEs) have begun to receive attention as an emerging risk environment for transmission and acquisition of HIV and other sexually transmitted diseases (STDs) among MSM. A GSE has been defined as ''a threesome….or larger gathering in which participants get together for the express purpose of having sex'' [11] and can include group sexual activity at a personal home or a privately organized sex party, as well as at other sex-onpremises venues (SOPVs), such as bathhouses, sex clubs, and public sex areas [12,13]. High levels of sexual risk behavior among MSM have been documented within GSE contexts [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A GSE has been defined as ''a threesome….or larger gathering in which participants get together for the express purpose of having sex'' [11] and can include group sexual activity at a personal home or a privately organized sex party, as well as at other sex-onpremises venues (SOPVs), such as bathhouses, sex clubs, and public sex areas [12,13]. High levels of sexual risk behavior among MSM have been documented within GSE contexts [11][12][13][14]. For example, in two recent studies more than one-fifth of MSM who reported engaging in group sex within the previous 30 days indicated they had unprotected sex with non-regular, HIV unknown or HIV serodiscordant partners at their most recent group encounter [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation